PENGARUH TINGKAT SUKU BUNGA, DIVIDEND PAYOUT RATIO, EARNING PER SHARE DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2019 - faradila meirisa; Maria Meilita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
This study aims to examine the efferct of Interest Rates, Dividend Payout Ratio, Earning Per Share and Price to Book Value on Stock Prices in Property and Real Estate companies listed on the Stock Exchange Indonesia Period 2013 – 2019. The population on this study amounted to 65 property and real estate companies listed on the Indonesia Stock Exchange period 2013 – 2019. The sample in this study amounted to 10 property and real estate companies using the purposive sampling method. This study uses multiple regression analysis techniques to test hypoytheses. The test result partialli show that Interest Rates and Dividend Payout Ratio variabel have no effect and have no significant on stock prices, while Earning Per Share and Price to Book Value have a significant positive effect on stock prices. Simultaneously the variable Interest Rates, Dividend Payout Ratio, Earning Per Share and Price to Book Value together have a significant effect on Stock Price.